The differential effect of optogenetic serotonergic manipulation on sustained motor actions and waiting for future rewards in mice - Taira, Masakazu; Miyazaki, Kayoko W.; Miyazaki, Katsuhiko; Chen, Jianning; Okitsu-Sakurayama, Shiho; Chaudhary, Anupama; Nishio, Mika; Miyake, Tsukasa; Yamanaka, Akihiro; Tanaka, Kenji F.; Doya, Kenji (Frontiers in Neuroscience, 2024)
Serotonin is an essential neuromodulator that affects behavioral and cognitive functions. Previous studies have shown that activation of serotonergic neurons in the dorsal raphe nucleus (DRN) promotes patience to wait for future rewards. However, it is still unclear whether serotonergic neurons also regulate persistence to act for future rewards. Here we used optogenetic activation and inhibition of DRN serotonergic neurons to examine their effects on sustained motor actions for future rewards. We trained mice to perform waiting and repeated lever-pressing tasks with variable reward delays and tested effects of optogenetic activation and inhibition of DRN serotonergic neurons on task performance. Interestingly, in the lever-pressing task, mice tolerated longer delays as they repeatedly pressed a lever than in the waiting task, suggesting that lever-pressing actions may not simply be costly, but may also be subjectively rewarding. Optogenetic activation of DRN serotonergic neurons prolonged waiting duration in the waiting task, consistent with previous studies. However, its effect on lever presses was nuanced, and was detected only by focusing on the period before premature reward check and by subtracting the trends within and across sessions using generalized linear model. While optogenetic inhibition decreased waiting, it did not affect lever pressing time or numbers. These results revealed that the necessity of motor actions may increase motivation for delayed rewards and that DRN serotonergic neurons more significantly promote waiting rather than persistent motor actions for future rewards.